Sr2Fe1+xRe1−xO6 double perovskites: magnetoresistance and (magneto)thermopower. Issue 42 (2nd May 2019) - Maignan, Antoine; Martin, Christine; Lebedev, Oleg; Sottmann, Jonas; Nataf, Lucie; Baudelet, François; Hébert, Sylvie; Carbonio, Raúl E.
Abstract : Polycrystalline Sr2 Fe1+ x Re1− x O6 samples have been synthesized, structurally characterized by X-ray powder diffraction, transmission electron microscopy, X-ray absorption spectroscopy, and measurements of their magnetotransport properties were performed. Abstract : Polycrystalline Sr2 Fe1+ x Re1− x O6 samples have been synthesized and structurally characterized by X-ray powder diffraction, transmission electron microscopy and X-ray absorption spectroscopy. Resistivity strongly increases with x, but a large and negative magnetoresistance persists up to x = 0.33. This is discussed considering the charge delocalization in iron and rhenium t2g orbitals.